dinâmica da vegetação durante o quaternário tardio no limite continental da península bragantina, litoral amazônico - MACIEL, Giordana Leticia Monteiro (Universidade Federal do Pará, 2023)
The eastern Amazonian region is dominated and shaped by a macrotidal regime, harboring environments such as muddy plains colonized by mangroves, estuaries associated with tidal channels, floodplains, and macrotidal beaches, among others. To understand the vegetation dynamics and carry out the paleoenvironmental reconstitution in an Amazonian floodplain, palynological, sedimentary, and C-14 dating data were integrated based on a subsurface sedimentary profile collected in the region of the Taperaçu’s herbaceous fields, in the Bragança peninsula (PA), on the Amazon coast. The present study identified three fácies associations and four pollen zones that occurred during the Late Pleistocene and Holocene. The first facies association is defined as an alluvial deposit, which presented pelite facies, flaser heterolithic bedding with a coarsening upward sequence. The vegetation was predominantly typical of trees and shrubs, marked by the presence of Rubiaceae, Agavaceae, and Annonaceae families and with low herbaceous vegetation dominated by the Araceae family developed around 41,200- 39,975 cal years BP. The second facies association identified showed typical characteristics of a tidal channel, with a well-delimited erosive surface, which marks a transition in the processes operating over this environment; it comprises gravel, massive sand, and wavy-marked mud facies. Toward the Taperaçu’s tidal channel, herbaceous vegetation was developed, represented by Cyperaceae and Ulmaceae, and the presence of trees and shrubs, such as Arecaceae, Malphighiaceae, and Rubiaceae. During the early and mid-Holocene (6000-5915 cal years BP), at a depth of 6.45 m from the surface, the results revealed the formation of a tidal flat. The main pollen result during this phase was the establishment of mangroves, colonized by Rhizophora and Avicennia, in addition to the presence of herbaceous vegetation, which currently occupies the studied region, marking the late Holocene.